TFG binds LC3C to regulate ULK1 localization and autophagosome formation. (1st May 2021) - Carinci, Marianna; Testa, Beatrice; Bordi, Matteo; Milletti, Giacomo; Bonora, Massimo; Antonucci, Laura; Ferraina, Caterina; Carro, Marta; Kumar, Mukesh; Ceglie, Donatella; Eck, Franziska; Nardacci, Roberta; et al.
Abstract: The early secretory pathway and autophagy are two essential and evolutionarily conserved endomembrane processes that are finely interlinked. Although growing evidence suggests that intracellular trafficking is important for autophagosome biogenesis, the molecular regulatory network involved is still not fully defined. In this study, we demonstrate a crucial effect of the COPII vesicle‐related protein TFG (Trk‐fused gene) on ULK1 puncta number and localization during autophagy induction. This, in turn, affects formation of the isolation membrane, as well as the correct dynamics of association between LC3B and early ATG proteins, leading to the proper formation of both omegasomes and autophagosomes. Consistently, fibroblasts derived from a hereditary spastic paraparesis (HSP) patient carrying mutated TFG (R106C) show defects in both autophagy and ULK1 puncta accumulation. In addition, we demonstrate that TFG activity in autophagy depends on its interaction with the ATG8 protein LC3C through a canonical LIR motif, thereby favouring LC3C‐ULK1 binding. Altogether, our results uncover a link between TFG and autophagy and identify TFG as a molecular scaffold linking the early secretion pathway to autophagy. Synopsis: TFG (Trk‐fused gene) is a resident protein of the interface between endoplasmic reticulum (ER) and ER‐Golgi intermediate compartment (ERGIC), coordinating the distribution of COPII vesicles between the two compartments. This study reveals that, upon starvation‐induced autophagy, TFG regulates autophagosome formation in mammalian cells by acting on the ULK1‐LC3C axis. TFG is required for correct ULK1 localization and stability upon autophagy induction. TFG facilitates ULK1 interaction with LC3C to modulate omegasome and autophagosome formation. TFG interacts with LC3C via its canonical LIR motif, favouring LC3C binding to ULK1. Fibroblasts derived from a Hereditary spastic paraparesis (HSP) patient carrying mutated TFG (R106C) show defective ULK1 puncta accumulation and autophagy.. Abstract : Trk‐fused gene (TFG) acts as a molecular scaffold linking the early secretory pathway and autophagy in mammalian cells.